Comparing social sustainability assessment indicators and tools for bio-districts: building an analytical framework - Packer, Giacomo; Zanasi, Cesare (Frontiers in Sustainable Food Systems, 2023)
Bio-districts are a practical example of a sustainable food system, which uses agroecological principles as tools for rural development. This research aims to understand the role of bio-districts in sustainable development, particularly in relation to social impacts. It does so by developing a framework for assessing social impacts in the context of alternative food systems. To this end, a two-step methodology is adopted. In the first part, a systematic literature review is carried out according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. It presents the state of the art in social impact assessment of bio-districts, identifying the approaches and indicators used to assess social standards, codes of good practice and, more generally, the factors influencing social sustainability in rural areas. In addition, a set of social themes is developed and validated through a content analysis to uncover the trends in the debate on social sustainability in bio-districts. In the second part, promising analytical frameworks and tools from the literature are compared on the basis of how deeply they assess social issues related to bio-districts. Finally, a description of the main steps that should be taken to adapt existing tools and frameworks to the local context is presented. A detailed framework specifically addressing the social impacts of bio-districts was not found in the literature. IDEA, MOTIFS, PG tools, RISE, SAFA guidelines, SOAAN guidelines and S-LCA are considered a suitable starting point for the bio-districts’ analysis, although tailored adjustments are required.